2015
DOI: 10.1186/s13395-016-0075-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE:Exercise-induced mitochondrial p53 repairs mtDNA mutations in mutator mice

Abstract: BackgroundHuman genetic disorders and transgenic mouse models have shown that mitochondrial DNA (mtDNA) mutations and telomere dysfunction instigate the aging process. Epidemiologically, exercise is associated with greater life expectancy and reduced risk of chronic diseases. While the beneficial effects of exercise are well established, the molecular mechanisms instigating these observations remain unclear.ResultsEndurance exercise reduces mtDNA mutation burden, alleviates multisystem pathology, and increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 42 publications
(88 reference statements)
2
64
0
Order By: Relevance
“…Increased oxidative stress in the mitochondria of the PolG mouse also induces nuclear DNA damage, as represented by telomere erosion [16••], which in turn facilitates translocation of the tumor suppressor protein, p53, into the nucleus from its cytoplasmic depots [17]. Indeed, we clearly observed elevated nuclear p53 levels in the sedentary PolG mouse, in tandem with nuclear DNA damage [16••].…”
Section: Polg Phenotype and Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased oxidative stress in the mitochondria of the PolG mouse also induces nuclear DNA damage, as represented by telomere erosion [16••], which in turn facilitates translocation of the tumor suppressor protein, p53, into the nucleus from its cytoplasmic depots [17]. Indeed, we clearly observed elevated nuclear p53 levels in the sedentary PolG mouse, in tandem with nuclear DNA damage [16••].…”
Section: Polg Phenotype and Oxidative Stressmentioning
confidence: 99%
“…Indeed, we clearly observed elevated nuclear p53 levels in the sedentary PolG mouse, in tandem with nuclear DNA damage [16••]. Nuclear p53 has been shown to activate senescence and apoptosis programs in both somatic and stem cells [17].…”
Section: Polg Phenotype and Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…In the mtDNA mutator mouse, endurance exercise improves oxidative capacity, prevents or repairs mtDNA depletion and mutations through tumor suppressor protein p53 and increases lifespan (Safdar et al, 2011; Safdar et al, 2015). However, others have reported that although oxidative capacity is improved, there are no changes in the mtDNA mutation load (Jeppesen et al, 2009; Taivassalo et al, 2006).…”
Section: Interventions To Attenuate the Symptoms Of Agingmentioning
confidence: 99%